IS THE WRITER A LOAFER OR ON THE SOCIAL BENEFITS OF DOING NOTHING. THE PROSE OF SRĐAN VALJAREVIĆ - Nowak-Bajcar, Sylwia (Porównania, 2019)
The category of authenticity, which was scientifically discussed by Lionel Trilling in his book Sincerity and authenticity from 1972, is the starting point for considering Srđan Valjarević’s prose. Referring to the values on which he built his philosophy of sentimentality, the Serbian writer (born in 1967) attempts to find a new lyrical language for describing the surrounding world. For this reason, his achievements can be described as a “new sensibility”. This new form of altruism, a form that allows the artist “to be themselves” is an alternative to the forms of ostentatious social involvement. Based on the individuality the “subtler language” of the weak subjectivity is – according to Valjarević – able to resist the problems and crises of the modern world.